Streamlined inactivation, amplification, and Cas13-based detection of SARS-CoV-2 - Jon Arizti-Sanz (Nature Portfolio, 2020)
The COVID-19 pandemic has highlighted the need for user-friendly diagnostic techniques. Here, the authors present SHINE, a streamlined and optimised Cas13-based method with accompanying smartphone app for visual diagnosis.